Assesment of User Satisfaction of Accredited Government Hospital Services in Palembang Using the SERVQUAL Approach - Fildzah Hashifah Taufiq; Muhammad Zulkarnain; Misnaniarti Misnaniarti (Faculty of Economics, Universitas Sriwijaya, 2023)
The purpose of this study was to analyze the service quality of government hospitals in Palembang based on the user's perspective and the determining factors as well as the influence of service quality on service user satisfaction of government hospitals in Palembang. The population of this study is all patients in three public hospitals in Palembang. The sample was calculated using the Lemeshow formula with total respondents of 100 patients. The data is obtained through questionnaires using SERVQUAL method. The results show that, service quality that measured by dimensions of tangibility, empathy, reliability, responsiveness and assurances is found to be lower than the patients’ expectations. The results also show that service quality has a positive and significant effect on user satisfaction on the government hospitals in Palembang.